Microemulsão: Um promissor carreador para moléculas insolúveis - Damasceno, B. P G L; Silva, J. A.; Oliveira, E. E.; Silveira, W. L L; Araújo, I. B.; Oliveira, Anselmo Gomes de [UNESP]; Egito, E. S T (My University, 2011)
Microemulsions (ME) are thermodynamically stable and isotropic systems of two immiscible liquids (oil/water), stabilized by an interfacial film of surfactants, discovered by Hoar and Schulman in 1943. The study of ME formation is based on three areas of theory: (1) solubilization, (2) interfacial tension and (3) thermodynamics. ME structures are influenced by the physicochemical properties and proportions of their ingredients. The goal of this review is to assess the state of the art of microemulsified systems, from a theoretical viewpoint. Also, recent progress on their clinical application and use as carriers for insoluble compounds is discussed.

Microemulsão (ME) é um sistema que foi descoberto por Hoar e Schulman no ano de 1943 e que é termodinamicamente estável e isotropicamente translúcido de dois líquidos imiscíveis (óleo/água), estabilizados por um filme interfacial de tensoativos. O estudo de sistemas microemulsionados se baseia nas suas três teorias de formação: (1) teoria da solubilização, (2) teoria da tensão interfacial e (3) teoria termodinâmica. A estrutura formada é influenciada pelas propriedades físico-químicas dos componentes utilizados e da razão entre os componentes. O objetivo desta revisão foi avaliar o estado da arte de sistemas microemulsionados enfatizando uma abordagem teórica. Além disso, os recentes avanços sobre a aplicabilidade clínca e utilização como carreador de moléculas insolúveis foram discutidas.
Microemulsion: A promising carrier system for insoluble compounds
Keywords: Microemulsion; Pharmaceutical Application; Phase Diagram; surfactant; microemulsion; physical chemistry; review; solubilization; surface tension; thermodynamics